Integration of Project-Based Collaborative Learning Model to Improve Critical Thinking and Psikosocial Skills of Junior High School Students - Wahyuningrum, Paulina Maria Ekasari; Winei, Agnes Angi Dian; Jumrio, Edy; Sawo, Emilianus Sember (Bulletin of Counseling and Psychotherapy, 2023)
Critical thinking and pschosocial skill are the abilites to achieve in 21st century. One effort to improve these abilities can be through project-based collaborative learning (PjBL). This quantitative study aims to determine the integration of the PBCL model on students' critical thinking and psychosocial skill on the Catholic Religious Education subjects. This research used a pre test and post test design. The research population were the eighth students of junior high school from three schools in Palangkaraya, totaling 30 students. The research instrument used 30 questions for critical thinking skill and 30 questions for psychosocial skill. The collected data was then analyzed using the t- test. The results of the analysis show that the PBCL model has a significant effect on students' critical thinking abilities and psychosocial skills on the on the Catholic Religious Education subjects. Thus, the PBCL model can be used as an alternative learning to improve critical thinking abilities and psychosocial skills